Biomechanical analysis of sandwich vertebrae in osteoporotic patients: finite element analysis - Huang, Shaolong; Zhou, Chengqiang; Zhang, Xu; Tang, Zhongjian; Liu, Liangyu; Meng, Xiao; Xue, Cheng; Tang, Xianye (Frontiers in Endocrinology, 2023)
Abstract Objective: The aim of this study was to investigate the biomechanical stress of sandwich vertebrae (SV) and common adjacent vertebrae in different degrees of spinal mobility in daily life. Materials and methods: We developed and validated a finite element model of the spinal segment of T10-L2. Simultaneously, T11 and L1 fractures were simulated, and a 6 mL bone cement was constructed in their center. Under the condition of applying a 500N axial load to the upper surface of T10 and immobilizing the lower surface of L2, moments were applied to the upper surface of T10, T11, T12, L1, and L2 and divided into five groups: M-T10, M-T11, M-T12, M-L1, and M-L2. The maximum von Mises stress of T10, T12, and L2 in different groups was calculated and analyzed. Results: The maximum von Mises stress of T10 in the M-T10 group was 30.68, 36.13, 34.27, 33.43, 26.86, and 27.70 MPa greater than the maximum stress value of T10 in the other groups in six directions of load flexion, extension, left and right lateral bending, and left and right rotation, respectively, and the T12 stress value in the M-T12 group was 29.62, 32.63, 30.03, 31.25, 26.38, and 26.25 MPa greater than the T12 stress value in the other groups in six directions. The maximum stress of L2 in M-T12 in the M-L2 group was 25.48, 36.38, 31.99, 31.07, 30.36, and 32.07 MPa, respectively, which was greater than the stress value of L2 in other groups. When the load is on which vertebral body it is subjected to the greatest stress. Conclusion: We found that SV did not always experience the highest stress. The most stressed vertebrae vary with the degree of curvature of the spine. Patients should be encouraged to avoid the same spinal curvature posture for a long time in life and work or to wear a spinal brace for protection after surgery, which can avoid long-term overload on a specific spine and disrupt its blood supply, resulting in more severe loss of spinal quality and increasing the possibility of fractures.